The Attitude, Knowledge, and Evaluation of Herbal Medicinal Products for Respiratory Diseases in Northern Cyprus among Pharmacists, Patients, and Pulmonologists - Dumenci, Mehmet; Mericli, Filiz; Tosun, Özgur; Yavuz, Dudu Özkum (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: The utilization of Complementary and Alternative Medicine (CAM) has grown remarkably over the years as people seek alternative treatment methods to conventional medicine to manage various health conditions. Aim: The study aimed to assess the utilization of herbal remedies in treating respiratory disorders, enhance the safe and efficient use of herbal medicinal products, and raise awareness of the effectiveness of CAM in respiratory tract diseases in Northern Cyprus. Materials and Methods: The study was conducted on 610 respiratory patients, 10 pulmonologists, and 150 pharmacists, who participated voluntarily in the survey. The data was collected through three tailored questionnaires distributed to the target participants face-to-face and online. The collected data were analyzed using the SPSS software. Results: The data obtained from the survey indicated that patients with lower income and educational attainment tend to use herbal medicinal products less frequently compared to those with higher income (p= 0.026) and educational levels (p= 0.003). Pharmacists aged under 45 were more knowledgeable about herbal medicinal products than pharmacists over 45 (p < 0.05). It was observed that a substantial majority (96%) of pharmacists recommend herbal medicinal products to their patients, primarily for preventive purposes. Additionally, pulmonologists lacked knowledge of herbal medicinal compositions, posology, administration, indications, side effects, and usage warnings. Conclusion: The study highlights the lack of adequate information among pharmacists, patients and pulmonologists regarding using herbal medicinal products for respiratory diseases. There is a pressing need for seminars and credible resources to address this knowledge deficit.
Keywords: Complementary and Alternative Medicine; Pharmacists; Herbal Medicinal Products; Respiratory Diseases